High-tap-density hard carbon material and preparation method and application thereof

By surface oxidation and polyethyleneimine grafting treatment of scale graphite powder, combined with tableting and high-temperature carbonization treatment, high-tap density hard carbon materials were prepared, solving the battery performance problems caused by low-tap density of existing hard carbon materials. , significantly improves the electrochemical performance and energy density of sodium ion batteries.

CN119409173APending Publication Date: 2025-02-11CNBM ZHEJIANG MATERIAL TECH CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411869587.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

Due to the low tap density in sodium ion batteries, existing hard carbon materials have insufficient contact between the active substances of the negative electrode sheet and the component particles, which increases the consumption of electrolyte, reduces the initial Coulomb efficiency and reversible capacity of the battery, affecting the The energy density of sodium ion batteries.

Method used

By using concentrated nitric acid to surface oxidize the scale graphite powder and graft polyethyleneimine on the surface of the scale graphite powder, it improves its dispersion in epoxy resin and carbon layer rearrangement behavior, and adjusts the pores of hard carbon materials. The structure was then subjected to tableting and high-temperature carbonization to prepare a high-tap density hard carbon material.

Benefits of technology

The tap density and electrochemical performance of hard carbon materials are improved, the first Coulomb efficiency and reversible capacity of the negative electrode material of sodium ion battery are enhanced, and the energy density of sodium ion battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005195427810000081
    Figure BDA0005195427810000081
  • Figure BDA0005195427810000091
    Figure BDA0005195427810000091
Patent Text Reader

Abstract

The invention discloses a high-tap-density hard carbon material and a preparation method and application thereof.According to the high-tap-density hard carbon material and the preparation method and application thereof, crystalline flake graphite powder is subjected to surface oxidation treatment through concentrated nitric acid, then polyethyleneimine is grafted to the surface of the crystalline flake graphite powder, and the dispersity of the crystalline flake graphite powder in epoxy resin is improved; meanwhile, the long-chain alkyl structure of the polyethyleneimine can promote the rearrangement of a carbon layer in the carbonization process and adjust the pore structure of the hard carbon material, so that the electrochemical performance of the hard carbon material is improved; in addition, the polyethyleneimine contains a large number of amino groups, and the electrochemical performance of the hard carbon material is further improved through nitrogen doping; then, the carbonized material is subjected to tabletting treatment, carbonized material particles are rearranged again, particle gaps are further reduced, a compact stacking state is formed, meanwhile, under the action of pressure, part of the particles deform, the grading effect is better after high-temperature calcination, and the effect of improving the tap density of the material is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery materials, and in particular to a hard carbon material with high tap density and a preparation method and application thereof. Background Art

[0002] Sodium ion batteries (SIBs) work similarly to lithium ion batteries (LIBs) and are considered to be one of the most likely alternatives to lithium ion batteries in the energy storage field due to their higher cost-effectiveness. + Radius ratio Li + The radius is larger, and traditional graphite negative electrode materials are not sufficient to meet the embedding / ejection of sodium ions during the charge and discharge process. As a typical amorphous carbon material, hard carbon has a large interlayer spacing (more than 0.37nm) and abundant energy storage sites, and is the most promising SIB negative electrode material. However, hard carbon usually has a low tap density, which makes it lack a good compaction density. This leads to the inability of the active material and the particles of each component of the negative electrode sheet to fully contact each other during the rolling process. Instead, it increases the contact area with the electrolyte, resulting in the consumption of sodium ions and electrolyte, thereby reducing the initial coulombic efficiency and reversible capacity of the battery, and causing a large loss of active sodium. In addition, the lower compaction density will greatly reduce the energy density of sodium-ion batteries, affecting their inability to be commercialized on a large scale.

[0003] Chinese patent publication CN115849332A discloses a high-rate hard carbon negative electrode material and a preparation method thereof. The method uses a biomass polymer as a hard carbon precursor, mixes it with anhydride organic matter through a solvent method, and utilizes the soft carbon properties of the anhydride organic matter to induce the hard carbon to grow a graphite microcrystalline structure and fill the hard carbon pores to form partial closed pores to increase the sodium storage capacity, thereby achieving high initial efficiency, high-rate performance and stable sodium ion storage, but its capacity is relatively low and still needs to be further improved. Summary of the invention

[0004] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a high tap density hard carbon material and a preparation method and application thereof. The hard carbon material prepared by the present invention has a high tap density and has excellent electrochemical properties when used to prepare sodium ion battery negative electrode materials.

[0005] In order to achieve the above object, the present invention adopts the following technical scheme:

[0006] A method for preparing a hard carbon material with high tap density comprises the following steps:

[0007] S1. Preparation of pretreated flake graphite powder

[0008] The flake graphite powder is added into concentrated nitric acid, heated and stirred, and then filtered, washed and dried to obtain pretreated flake graphite powder.

[0009] In this step, the usage ratio of flake graphite powder and concentrated nitric acid is 10-15g:100mL.

[0010] In this step, the temperature of the heating and stirring treatment is 50-80°C, and the time of the heating and stirring treatment is 1-3h.

[0011] In this step, the surface of the flake graphite powder is oxidized by using concentrated nitric acid, in order to increase the surface activity of the flake graphite powder and facilitate the subsequent reaction.

[0012] S2. Preparation of modified flake graphite powder

[0013] The pretreated flake graphite powder is dispersed in deionized water, the pH of the solution is adjusted to 9-12, and then polyethyleneimine and epichlorohydrin are added thereto, heated and stirred for reaction, and after the reaction is completed, the modified flake graphite powder is obtained by filtering, washing and drying.

[0014] In this step, the mass ratio of the pretreated flake graphite powder, polyethyleneimine and epichlorohydrin is 10-15:5-10:4-8.

[0015] In this step, the temperature of the heating and stirring reaction is 70-90°C, for example, 70°C, 75°C, 80°C, 85°C, and 90°C can be selected; the time of the heating and stirring reaction is 3-5h, for example, 3h, 3.5h, 4h, 4.5h, and 5h can be selected, but it is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0016] In this step, the pretreated flake graphite powder is modified and polyethyleneimine is grafted onto the surface of the flake graphite powder, thereby improving the dispersibility of the flake graphite powder in the epoxy resin. At the same time, the long-chain alkyl structure of polyethyleneimine can effectively control the rearrangement behavior of the carbon layer during the carbonization process, adjust the pore structure of the hard carbon material, and thus improve the electrochemical properties of the hard carbon material. In addition, polyethyleneimine contains a large number of amino groups, and the electrochemical properties of the hard carbon material are further improved by nitrogen doping.

[0017] S3. Preparation of hard carbon precursor

[0018] The modified flake graphite powder is added into the epoxy resin and dispersed evenly, and then a curing agent is added, and a hard carbon precursor is obtained after curing and cross-linking.

[0019] In this step, the mass ratio of the modified flake graphite powder, the epoxy resin and the curing agent is 2-4:50:5-8.

[0020] Specifically, the epoxy resin is selected from epoxy resin E44 or epoxy resin E51.

[0021] Specifically, the curing agent is selected from ethylenediamine.

[0022] In this step, the curing and cross-linking temperature is 60-75°C, for example, 60°C, 65°C, 70°C, 75°C can be selected; the curing and cross-linking time is 1-2h, for example, 1h, 1.5h, 2h can be selected; but it is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0023] In this step, by adding the modified flake graphite powder into the epoxy resin, the epoxy groups in the epoxy resin and the amino groups in the modified flake graphite powder are chemically cross-linked, thereby improving the cross-linking density and conductive properties of the epoxy resin material, thereby improving the density and electrochemical properties of the hard carbon material.

[0024] S4. Preparation of carbonized material

[0025] The hard carbon precursor is subjected to low-temperature carbonization treatment under an inert gas, and then ground and sieved to obtain a carbonized material.

[0026] In this step, the inert gas may be nitrogen or argon.

[0027] The temperature of low-temperature carbonization treatment is 400-600°C, for example, 400°C, 450°C, 500°C, 550°C, and 600°C can be selected; the heating rate is 5-10°C / min, for example, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, and 10°C / min can be selected; the holding time is 2-3h, for example, 2h, 2.5h, and 3h can be selected, but it is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0028] S5. Preparation of high tap density hard carbon materials

[0029] The carbonized material is subjected to tabletting treatment and then subjected to high-temperature carbonization treatment under an inert gas to obtain a hard carbon material with a high tap density.

[0030] In this step, the tableting treatment pressure is 15-25 MPa, for example, 15 MPa, 16 MPa, 17 MPa, 18 MPa, 19 MPa, 20 MPa, 21 MPa, 22 MPa, 23 MPa, 24 MPa, 25 MPa can be selected; the tableting treatment time is 10-20 min, for example, 10 min, 12 min, 15 min, 18 min, 20 min can be selected; but it is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0031] In this step, the inert gas may be nitrogen or argon.

[0032] In this step, the temperature of high-temperature carbonization treatment is 900-1200°C, for example, 900°C, 950°C, 1000°C, 1050°C, 1100°C, 1150°C, and 1200°C can be selected; the heating rate is 10-20°C / min, for example, 10°C / min, 11°C / min, 12°C / min, 13°C / min, 14°C / min, 15°C / min, 16°C / min, 17°C / min, 18°C / min, 19°C / min, and 20°C / min can be selected; the holding time is 2-3h, for example, 2h, 2.5h, and 3h can be selected; but it is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable.

[0033] In a second aspect, the present invention provides a hard carbon material with high tap density prepared by the above preparation method.

[0034] In a third aspect, the present invention also provides the use of the above-mentioned high tap density hard carbon material in battery negative electrode materials.

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] (1) The present invention uses concentrated nitric acid to perform surface oxidation treatment on flake graphite powder, the purpose of which is to increase the surface activity of the flake graphite powder and facilitate the subsequent reaction. Polyethyleneimine is then grafted onto the surface of the flake graphite powder to improve the dispersibility of the flake graphite powder in the epoxy resin. At the same time, the long-chain alkyl structure of polyethyleneimine can promote the rearrangement of the carbon layer during the carbonization process, regulate the pore structure of the hard carbon material, increase the tap density of the material, and thus improve the electrochemical properties of the hard carbon material. In addition, polyethyleneimine contains a large number of amino groups, and the electrochemical properties of the hard carbon material are further improved by nitrogen doping.

[0037] (2) The present invention performs tabletting on the carbonized material, so that the carbonized material particles are rearranged again, the gaps between the particles are further reduced, and a dense stacking state is formed. At the same time, under the action of pressure, some particles will deform, and the grading effect will be better after high-temperature calcination, thereby achieving the effect of improving the material's tap density.

[0038] (3) The hard carbon negative electrode material prepared by the present invention exhibits a high first coulombic efficiency and reversible capacity, and shows good electrical properties, which is beneficial to improving the electrochemical performance of the negative electrode side of the sodium ion battery during large-scale use, thereby improving the energy density of the sodium ion battery. DETAILED DESCRIPTION

[0039] The present invention is further described in detail below through specific preferred embodiments, but the present invention is not limited to the following embodiments.

[0040] It should be noted that, unless otherwise specified, the chemical reagents involved in the present invention were purchased through commercial channels.

[0041] The mesh number of the flake graphite powder used in the present invention is 2000 meshes; the relative molecular mass of polyethyleneimine is 3000, purchased from Shanghai Youen Chemical Co., Ltd.; and the mass fraction of concentrated nitric acid is 68%.

[0042] Example 1

[0043] A method for preparing a hard carbon material with high tap density comprises the following steps:

[0044] S1. Add 10 g of flake graphite powder to 100 mL of concentrated nitric acid, heat and stir at 50 °C for 3 h, then filter, wash and dry to obtain pretreated flake graphite powder;

[0045] S2, 10g of pretreated flake graphite powder was dispersed in 150mL of deionized water, the pH of the solution was adjusted to 10, and then 5g of polyethyleneimine and 4g of epichlorohydrin were added thereto, and the mixture was heated and stirred at 70°C for 5h. After the reaction was completed, the mixture was filtered, washed and dried to obtain modified flake graphite powder;

[0046] S3, adding 2g of modified flake graphite powder to 50g of epoxy resin E44, dispersing evenly, then adding 5g of curing agent ethylenediamine, curing and cross-linking at 60°C for 2h to obtain a hard carbon precursor;

[0047] S4, subjecting 20 g of the hard carbon precursor to low-temperature carbonization treatment in a nitrogen atmosphere at a temperature of 400° C., a heating rate of 5° C. / min, and a holding time of 2 h, and then grinding through a 400-mesh sieve to obtain a carbonized material;

[0048] S5. Put 20g of carbonized material into a tableting container for tableting treatment. The tableting treatment pressure is 15MPa and the tableting treatment time is 20min. Then, high-temperature carbonization treatment is carried out under a nitrogen atmosphere. The high-temperature carbonization treatment temperature is 900℃, the heating rate is 10℃ / min, and the insulation time is 2h to obtain a hard carbon material with high tap density.

[0049] Example 2

[0050] A method for preparing a hard carbon material with high tap density comprises the following steps:

[0051] S1. Add 15 g of flake graphite powder to 100 mL of concentrated nitric acid, heat and stir at 80 ° C for 1 h, then filter, wash and dry to obtain pretreated flake graphite powder;

[0052] S2, 12g of pretreated flake graphite powder was dispersed in 150mL of deionized water, the pH of the solution was adjusted to 10, and then 8g of polyethyleneimine and 6g of epichlorohydrin were added thereto, and the mixture was heated and stirred at 70°C for 5h. After the reaction was completed, the mixture was filtered, washed and dried to obtain modified flake graphite powder;

[0053] S3, adding 4g of modified flake graphite powder to 50g of epoxy resin E44, dispersing evenly, then adding 6g of curing agent ethylenediamine, curing and cross-linking at 60°C for 2h to obtain a hard carbon precursor;

[0054] S4, subjecting 20 g of the hard carbon precursor to low-temperature carbonization treatment in a nitrogen atmosphere at a temperature of 500° C., a heating rate of 5° C. / min, and a holding time of 2 h, and then grinding through a 400-mesh sieve to obtain a carbonized material;

[0055] S5. Put 20g of carbonized material into a tableting container for tableting treatment. The tableting pressure is 20MPa and the tableting time is 20min. Then, high-temperature carbonization treatment is carried out under nitrogen atmosphere. The temperature of high-temperature carbonization treatment is 1000℃, the heating rate is 10℃ / min, and the insulation time is 2h to obtain a hard carbon material with high tap density.

[0056] Example 3

[0057] A method for preparing a hard carbon material with high tap density comprises the following steps:

[0058] S1. Add 12 g of flake graphite powder to 100 mL of concentrated nitric acid, heat and stir at 60 ° C for 2 h, then filter, wash and dry to obtain pretreated flake graphite powder;

[0059] S2, 15g of pretreated flake graphite powder was dispersed in 150mL of deionized water, the pH of the solution was adjusted to 10, and then 10g of polyethyleneimine and 8g of epichlorohydrin were added thereto, and the mixture was heated and stirred at 90°C for 3h. After the reaction was completed, the mixture was filtered, washed and dried to obtain modified flake graphite powder;

[0060] S3, adding 2g of modified flake graphite powder to 50g of epoxy resin E51, dispersing evenly, then adding 5g of curing agent ethylenediamine, curing and cross-linking at 75°C for 1h to obtain a hard carbon precursor;

[0061] S4, subjecting 20 g of the hard carbon precursor to low-temperature carbonization treatment in a nitrogen atmosphere at a temperature of 500° C., a heating rate of 5° C. / min, and a holding time of 2 h, and then grinding through a 400-mesh sieve to obtain a carbonized material;

[0062] S5. Put 20g of carbonized material into a tableting container for tableting treatment. The tableting pressure is 25MPa and the tableting time is 20min. Then, high-temperature carbonization treatment is carried out under nitrogen atmosphere. The temperature of high-temperature carbonization treatment is 1200℃, the heating rate is 10℃ / min, and the insulation time is 2h to obtain a hard carbon material with high tap density.

[0063] Example 4

[0064] A method for preparing a hard carbon material with high tap density comprises the following steps:

[0065] S1. Add 10 g of flake graphite powder to 100 mL of concentrated nitric acid, heat and stir at 60 ° C for 2 h, then filter, wash and dry to obtain pretreated flake graphite powder;

[0066] S2, 12g of pretreated flake graphite powder was dispersed in 150mL of deionized water, the pH of the solution was adjusted to 10, and then 6g of polyethyleneimine and 6g of epichlorohydrin were added thereto, and the mixture was heated and stirred at 80°C for 4h. After the reaction was completed, the mixture was filtered, washed and dried to obtain modified flake graphite powder;

[0067] S3, adding 4g of modified flake graphite powder to 50g of epoxy resin E51, dispersing evenly, then adding 8g of curing agent ethylenediamine, curing and cross-linking at 75°C for 1h to obtain a hard carbon precursor;

[0068] S4, subjecting 20 g of the hard carbon precursor to low-temperature carbonization treatment in a nitrogen atmosphere at a temperature of 600° C., a heating rate of 5° C. / min, and a holding time of 2 h, and then grinding through a 400-mesh sieve to obtain a carbonized material;

[0069] S5. Put 20g of carbonized material into a tableting container for tableting treatment. The tableting pressure is 20MPa and the tableting time is 20min. Then, high-temperature carbonization treatment is carried out under nitrogen atmosphere. The temperature of high-temperature carbonization treatment is 1000℃, the heating rate is 15℃ / min, and the insulation time is 2h to obtain a hard carbon material with high tap density.

[0070] Comparative Example 1

[0071] A method for preparing a hard carbon material with high tap density comprises the following steps:

[0072] S1. Add 2 g of flake graphite powder to 50 g of epoxy resin E44 and disperse evenly, then add 5 g of curing agent ethylenediamine, and cure and crosslink at 60° C. for 2 h to obtain a hard carbon precursor;

[0073] S2, subjecting 20 g of hard carbon precursor to low-temperature carbonization treatment in a nitrogen atmosphere at a temperature of 400° C., a heating rate of 5° C. / min, and a holding time of 2 h, and then grinding through a 400-mesh sieve to obtain a carbonized material;

[0074] S3. Put 20g of carbonized material into a tableting container for tableting treatment. The tableting treatment pressure is 15MPa and the tableting treatment time is 20min. Then, high-temperature carbonization treatment is carried out under a nitrogen atmosphere. The high-temperature carbonization treatment temperature is 900℃, the heating rate is 10℃ / min, and the insulation time is 2h to obtain a high tap density hard carbon material.

[0075] Compared with Example 1, Comparative Example 1 does not perform modification treatment on the flake graphite powder.

[0076] Comparative Example 2

[0077] A method for preparing a hard carbon material with high tap density comprises the following steps:

[0078] S1. Add 10 g of flake graphite powder to 100 mL of concentrated nitric acid, heat and stir at 50 °C for 3 h, then filter, wash and dry to obtain pretreated flake graphite powder;

[0079] S2, 10g of pretreated flake graphite powder was dispersed in 150mL of deionized water, the pH of the solution was adjusted to 10, and then 5g of diethylenetriamine and 4g of epichlorohydrin were added thereto, and the mixture was heated and stirred at 70°C for 5h. After the reaction was completed, the mixture was filtered, washed and dried to obtain modified flake graphite powder;

[0080] S3, adding 2g of modified flake graphite powder to 50g of epoxy resin E44, dispersing evenly, then adding 5g of curing agent ethylenediamine, curing and cross-linking at 60°C for 2h to obtain a hard carbon precursor;

[0081] S4, subjecting 20 g of the hard carbon precursor to low-temperature carbonization treatment in a nitrogen atmosphere at a temperature of 400° C., a heating rate of 5° C. / min, and a holding time of 2 h, and then grinding through a 400-mesh sieve to obtain a carbonized material;

[0082] S5. Put 20g of carbonized material into a tableting container for tableting treatment. The tableting treatment pressure is 15MPa and the tableting treatment time is 20min. Then, high-temperature carbonization treatment is carried out under a nitrogen atmosphere. The high-temperature carbonization treatment temperature is 900℃, the heating rate is 10℃ / min, and the insulation time is 2h to obtain a hard carbon material with high tap density.

[0083] Compared with Example 1, in Comparative Example 2, polyethyleneimine is replaced by diethylenetriamine with a short carbon chain.

[0084] Comparative Example 3

[0085] A method for preparing a hard carbon material with high tap density comprises the following steps:

[0086] S1. Add 10 g of flake graphite powder to 100 mL of concentrated nitric acid, heat and stir at 50 °C for 3 h, then filter, wash and dry to obtain pretreated flake graphite powder;

[0087] S2, 10g of pretreated flake graphite powder was dispersed in 150mL of deionized water, the pH of the solution was adjusted to 10, and then 5g of polyethyleneimine and 4g of epichlorohydrin were added thereto, and the mixture was heated and stirred at 70°C for 5h. After the reaction was completed, the mixture was filtered, washed and dried to obtain modified flake graphite powder;

[0088] S3, adding 2g of modified flake graphite powder to 50g of epoxy resin E44, dispersing evenly, then adding 5g of curing agent ethylenediamine, curing and cross-linking at 60°C for 2h to obtain a hard carbon precursor;

[0089] S4, subjecting 20 g of the hard carbon precursor to low-temperature carbonization treatment in a nitrogen atmosphere at a temperature of 400° C., a heating rate of 5° C. / min, and a holding time of 2 h, and then grinding through a 400-mesh sieve to obtain a carbonized material;

[0090] S5. Carry out high-temperature carbonization treatment on 20 g of carbonized material in a nitrogen atmosphere at a temperature of 900° C., a heating rate of 10° C. / min, and a holding time of 2 h to obtain a hard carbon material with a high tap density.

[0091] Compared with Example 1, in Comparative Example 3, the carbonized material was not subjected to tableting treatment.

[0092] The hard carbon materials prepared in Examples 1-4 and Comparative Examples 1-3 were subjected to performance tests, and the specific steps were as follows:

[0093] Tap density test: Weigh 2 g of the hard carbon material samples obtained in Examples 1-4 and Comparative Examples 1-3 respectively and put them into a tap density tester, vibrate and rotate until the sample volume no longer decreases, and record the experimental data;

[0094] Electrochemical performance test: The hard carbon material and carboxymethyl cellulose were placed in a ball mill with a mass ratio of 9:1. Deionized water was added and the ball milling was performed for 2 hours. The rotation speed was set to 200 r / min. The slurry after ball milling was coated on the current collector copper foil. After vacuum drying at 100°C for 12 hours, it was cut into negative electrode sheets with a diameter of 12 mm. Metallic sodium was used as the counter electrode and reference electrode. A glass fiber diaphragm was used as the diaphragm. The electrolyte used was NaClO4 with a concentration of 1 mol / L. The solvent was a mixed solution of diethyl carbonate and ethylene carbonate (volume ratio of 1:1). The button cells were assembled in a glove box with a high-purity argon atmosphere.

[0095] The electrochemical performance test of the button cell prepared above was carried out under the following specific conditions:

[0096] The test was carried out on the Xinwei battery testing system. The charge and discharge voltage range was 0 to 2V, the current density was 1C, and 1C = 100mA / g.

[0097] The test results are shown in Table 1.

[0098] Table 1 Performance test results of different groups

[0099]

[0100]

[0101] It can be seen from the table that the electrochemical performance of the negative electrode material prepared from the hard carbon material in the embodiment of the present invention is significantly improved, and the capacity retention rate can still reach more than 90% after 100 cycles at a current density of 1C.

[0102] Finally, it should be noted that the above embodiments do not limit the present invention in any form. For those skilled in the art, some modifications and improvements can be made to the present invention. Therefore, any modification or improvement made without departing from the spirit of the present invention belongs to the scope of protection claimed in the present invention.

Claims

1. A method for preparing a hard carbon material with high tap density, characterized in that: The steps include: S1, adding the flake graphite powder to concentrated nitric acid, heating and stirring, then filtering, washing and drying to obtain pretreated flake graphite powder; S2, dispersing the pretreated flake graphite powder in deionized water, adjusting the pH of the solution to 9-12, then adding polyethyleneimine and epichlorohydrin thereto, heating and stirring to react, after the reaction is completed, filtering, washing and drying to obtain modified flake graphite powder; S3, adding the modified flake graphite powder to the epoxy resin, dispersing it evenly, then adding a curing agent, and obtaining a hard carbon precursor after curing and cross-linking; S4, subjecting the hard carbon precursor to low-temperature carbonization treatment under an inert gas, and then grinding and sieving to obtain a carbonized material; S5. The carbonized material is subjected to tabletting treatment, and then subjected to high-temperature carbonization treatment under an inert gas to obtain a hard carbon material with a high tap density.

2. The preparation method according to claim 1, characterized in that: In step S2, the mass ratio of the pretreated flake graphite powder, polyethyleneimine and epichlorohydrin is 10-15:5-10:4-8.

3. The preparation method according to claim 1, characterized in that: In step S2, the temperature of the heating and stirring reaction is 70-90° C., and the time of the heating and stirring reaction is 3-5 h.

4. The preparation method according to claim 1, characterized in that: In step S3, the mass ratio of the modified flake graphite powder, the epoxy resin and the curing agent is 2-4:50:5-8, wherein the curing agent is selected from ethylenediamine.

5. The preparation method according to claim 1, characterized in that: In step S3, the curing and cross-linking temperature is 60-75° C., and the curing and cross-linking time is 1-2 hours.

6. The preparation method according to claim 1, characterized in that: In step S4, the temperature of the low-temperature carbonization treatment is 400-600°C, the heating rate is 5-10°C / min, and the holding time is 2-3h.

7. The preparation method according to claim 1, characterized in that: In step S5, the tableting process is performed at a pressure of 15-25 MPa and for a time of 10-20 min.

8. The preparation method according to claim 1, characterized in that: In step S5, the temperature of the high-temperature carbonization treatment is 900-1200°C, the heating rate is 10-20°C / min, and the insulation time is 2-3h.

9. A hard carbon material with high tap density prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the high tap density hard carbon material as claimed in claim 9 in battery negative electrode materials.

Citation Information

Patent Citations

  • High-rate hard carbon negative electrode material and preparation method and application thereof

    CN115849332A